Non-Pharmacological Approaches in the Management of Primary Dysmenorrhea: A Literature Review - Mulyaningsih, Erika Agung; Juwita, septiana; Nahariani, Pepin; Mudhawaroh, Mudhawaroh (Jurnal Kebidanan dan Kesehatan Tradisional, 2025)
Background: The incidence of primary dysmenorrhea is a condition experienced by almost all adolescent women and of childbearing age, negatively impacting their quality of life and productivity. Although pharmacological treatments such as NSAIDs are frequently used, many individuals seek non-pharmacological alternatives to avoid long-term side effects. This study aims to explore the effectiveness of complementary therapies, including acupressure, herbal medicine, and yoga, in managing primary dysmenorrhea. Method: A systematic literature review (SLR) was conducted using the PRISMA approach, selecting relevant articles from PubMed, ScienceDirect, and Google Scholar based on specific keywords. Articles that met the inclusion criteria, such as publication range (2020-2025) and topic relevance, were further analyzed. Results: From a review of 17 articles that met the inclusion criteria, it was found that yoga can significantly reduce pain intensity by increasing relaxation and improving blood circulation in the pelvic area. Acupressure therapy, particularly on the SP6 point, has been proven effective in reducing menstrual pain by increasing the release of beta-endorphins. In addition, consumption of herbal medicines such as ginger has anti-inflammatory effects that help reduce the production of prostaglandins, one of the main causes of menstrual pain. Conclusion: Non-pharmacological therapies—such as yoga, acupressure, and herbal remedies—are effective, safe, and affordable alternatives to pharmacological management. It is recommended that healthcare professionals, particularly midwives, provide education and facilitate the implementation of these complementary therapies as part of promotive and preventive efforts to address menstrual pain in adolescents and women of childbearing age.